Active Expiration and the Measurement of Central Venous Pressure. (July 2018) - Magder, Sheldon; Serri, Karim; Verscheure, Sara; Chauvin, Renée; Goldberg, Peter
Purpose: To obtain a point prevalence estimate of alterations in central venous pressure (CVP) produced by active expiration in a consecutive series of intensive care patients. Methods: We evaluated CVP tracings taken by the nurses at their morning shift change in a consecutive series of 60 cardiac surgery and 59 noncardiac surgery patients. We also assessed change in values due to the change in transducer level. Three physicians and a nurse instructor independently reviewed the tracings and determined whether there was evidence of forced expiration and whether it was type A, defined by decreasing CVP during expiration, or type B, defined by increasing CVP during expiration. Results: Agreement for CVP value was 96% between a physician and a bedside nurse. Twenty-nine percent of participants had active expiration, evenly distributed between A and B types. Active expiration was not related to the type of surgery, use of bronchodilators, and the presence of chronic obstructive lung disease or abdominal distention. Active expiration was more common in nonventilated patients and patients not receiving vasopressor drugs, suggesting they were more awake. Conclusion: Active expiration is common in critically ill patients. Failure to recognize it can result in important errors in the estimation of CVP and other hemodynamic measurements.